Chitooligosaccharides Improves Severe Acute Pancreatitis by Reducing Intestinal Mucosal Injury and Regulating Intestinal Microbiota - Fanjun Meng; Guangchen Sun; Yan Zhao; Yayuan Luo; Yanou Bai; Weiyan Lyu; Hao Han; Xu Liu (Probiotics and Antimicrobial Proteins, 2026)

Enzyme-assisted extraction of proteins from radish leaf and their structure-function relationship in stabilizing high internal phase emulsions compared to soy protein and whey protein - Hang Wang; Fanjun Meng; Yinghan Zhao; Yang Liu; Jian Chen; Xiao Liu (Food Hydrocolloids, 2025)

Hollow porous Co0.85Se/MoSe2@MXene heterostructured anode for sodium-ion hybrid capacitors - Lu Shi; Fanjun Zhao; Yuan Tang; Ruixin Liu; Jie Pang; Guanggui Cheng; Meng Hu; Jianning Ding (Chemical Engineering Journal, 2024)

Genomic basis determining root system architecture in maize - Pengcheng Li; Zhihai Zhang; Gui Xiao; Zheng Zhao; Kunhui He; Xiaohong Yang; Qingchun Pan; Guohua Mi; Zhongtao Jia; Jianbing Yan; Fanjun Chen; Lixing Yuan (Theoretical and Applied Genetics, 2024)

Plasma cell-free DNA promise monitoring and tissue injury assessment of COVID-19 - Xin Jin; Yanqun Wang; Jinjin Xu; Yimin Li; Fanjun Cheng; Yuxue Luo; Haibo Zhou; Shanwen Lin; Fei Xiao; Lu Zhang; Yu Lin; Zhaoyong Zhang; et al. (Molecular Genetics and Genomics, 2023)
Coronavirus 2019 (COVID-19) is a complex disease that affects billions of people worldwide. Currently, effective etiological treatment of COVID-19 is still lacking; COVID-19 also causes damages to various organs that affects therapeutics and mortality of the patients. Surveillance of the treatment responses and organ injury assessment of COVID-19 patients are of high clinical value. In this study, we investigated the characteristic fragmentation patterns and explored the potential in tissue injury assessment of plasma cell-free DNA in COVID-19 patients. Through recruitment of 37 COVID-19 patients, 32 controls and analysis of 208 blood samples upon diagnosis and during treatment, we report gross abnormalities in cfDNA of COVID-19 patients, including elevated GC content, altered molecule size and end motif patterns. More importantly, such cfDNA fragmentation characteristics reflect patient-specific physiological changes during treatment. Further analysis on cfDNA tissue-of-origin tracing reveals frequent tissue injuries in COVID-19 patients, which is supported by clinical diagnoses. Hence, our work demonstrates and extends the translational merit of cfDNA fragmentation pattern as valuable analyte for effective treatment monitoring, as well as tissue injury assessment in COVID-19.

Mining genes regulating root system architecture in maize based on data integration analysis - Kunhui He; Zheng Zhao; Wei Ren; Zhe Chen; Limei Chen; Fanjun Chen; Guohua Mi; Qingchun Pan; Lixing Yuan (Theoretical and Applied Genetics, 2023)

Nitrogen responsiveness of leaf growth, radiation use efficiency and grain yield of maize (Zea mays L.) in Northeast China - Zheng Liu; Jia Gao; Siyu Zhao; Ye Sha; Yiwen Huang; Zhanhong Hao; Lihua Ke; Fanjun Chen; Lixing Yuan; Guohua Mi (Field Crops Research, 2023)

Dissecting the phenotypic response of maize to low phosphorus soils by field screening of a large diversity panel - Dongdong Li; Zhe Chen; Meng Wang; Willmar L. Leiser; Thea Mi Weiß; Zheng Zhao; Song Cheng; Shaojiang Chen; Fanjun Chen; Lixing Yuan; Tobias Würschum; Wenxin Liu (Euphytica, 2021)

Overexpression of the maize ZmAMT1;1a gene enhances root ammonium uptake efficiency under low ammonium nutrition - Yang Zhao; Zhi Liu; Fengying Duan; Xia An; Xiangguo Liu; Dongyun Hao; Riliang Gu; Zhangkui Wang; Fanjun Chen; Lixing Yuan (Plant Biotechnology Reports, 2018)